Clouds and hazes of Venus - Titov, D; Ignatiev, N; McGouldrick, K; Wilquet, V; Wilson, C (Springer Netherlands, 2018)
More than three decades have passed since the publication of the last review of the Venus clouds and hazes. The paper published in 1983 in the Venus book summarized the discoveries and findings of the US Pioneer Venus and a series of Soviet Venera spacecraft (Esposito et al. in Venus, p. 484, 1983). Due to the emphasis on in-situ investigations from descent probes, those missions established the basic features of the Venus cloud system, its vertical structure, composition and microphysical properties. Since then, significant progress in understanding of the Venus clouds has been achieved due to exploitation of new observation techniques onboard Galileo and Messenger flyby spacecraft and Venus Express and Akatsuki orbiters. They included detailed investigation of the mesospheric hazes in solar and stellar occultation geometry applied in the broad spectral range from UV to thermal IR. Imaging spectroscopy in the near-IR transparency “windows” on the night side opened a new and very effective way of sounding the deep atmosphere. This technique together with near-simultaneous UV imaging enabled comprehensive study of the cloud morphology from the cloud top to its deep layers. Venus Express operated from April 2006 until December 2014 and provided a continuous data set characterizing Venus clouds and hazes over a time span of almost 14 Venus years thus enabling a detailed study of temporal and spatial variability. The polar orbit of Venus Express allowed complete latitudinal coverage. These studies are being complemented by JAXA Akatsuki orbiter that began observations in May 2016. This paper reviews the current status of our knowledge of the Venus cloud system focusing mainly on the results acquired after the Venera, Pioneer Venus and Vega missions.